Pertimbangan Hakim Dalam Menjatuhkan Hukuman Kepada Anak Pelaku Tindak Pidana Pencurian Dengan Pemeberatan Di Peradilan Anak - Alkausar, Ilham; Rusli, Tami (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2021)
Children as gifts that are expected to be the successors of the family and nation sometimes do not match expectations with what is expected by both parents, often many crimes are committed by minors, crimes committed from the ordinary to extraordinary things, one of the crimes what is often done by minors is the crime of theft, there are many factors behind a minor committing a crime of theft that makes a child want to do it, one of which is bad environmental factors and family factors that pay less attention to the child, the judge's consideration is The most important thing in determining the realization of the value of a judge's decision is by looking at the existing facts.